Does team cohesion always positively influence team innovation? A chain mediation model - Zhang, Hua; Shi, Kun; Hu, Haoxiang (Advances in Social Sciences Research Journal, 2021)
This study explores the chain-mediating mechanism between organizational climate and team job crafting on team cohesion and team innovation behavior, based on the input-mediator-outcome-input (IMOI) theory .Using 229 valid samples, the result shows that team cohesion, organizational climate and team job crafting can significantly positively predict team innovation behavior; team job crafting plays an intermediary role between team cohesion and team innovation behavior; organizational climate and team job crafting play a chain mediating role between team cohesion and team innovation behavior. When other factors are taken into account, team cohesion is not always a positive factor in team innovation behavior This research attempted to combine the organizational factors with the mediating mechanism of team job crafting on team innovation behavior, and provide theoretical and practical guidance for the organizations on team innovation.